2011
DOI: 10.1159/000319789
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Monosymptomatic Patients with Hallucinations and Delusions in First-Episode Psychosis Patients: A Five-Year Longitudinal Follow-Up Study

Abstract: time to remission and suicidality. Results: Two groups of patients were identified; H (n = 16) and D (n = 106). 179 patients experienced both hallucinations and delusions (dual symptom group). The H group was significantly younger, had a longer duration of untreated psychosis, poorer premorbid function and better insight than the D group. Notably, the H group scored higher on measures of suicidality, and at 5 years follow-up a significantly higher proportion of patients was lost to suicide in this group. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 81 publications
4
6
0
1
Order By: Relevance
“…Our analysis showed that both Auditory Hallucinations score and Non-Auditory Hallucinations score were related to BIS total score. This result is in line with previous studies, though they compared patients with hallucinations only or with delusions only, and with both hallucinations and delusions or with neither of them (Evensen et al, 2011; Engh et al, 2010;). However, the first study involved only 16 first-episode psychosis patients experiencing hallucinations, and insight was measured only with the individual PANSS lack of judgment/insight item, and the second study relied on a sample with chronic psychotic disorders and used the Beck Cognitive Insight Scale.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our analysis showed that both Auditory Hallucinations score and Non-Auditory Hallucinations score were related to BIS total score. This result is in line with previous studies, though they compared patients with hallucinations only or with delusions only, and with both hallucinations and delusions or with neither of them (Evensen et al, 2011; Engh et al, 2010;). However, the first study involved only 16 first-episode psychosis patients experiencing hallucinations, and insight was measured only with the individual PANSS lack of judgment/insight item, and the second study relied on a sample with chronic psychotic disorders and used the Beck Cognitive Insight Scale.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding sociodemographic characteristics, female first-episode patients had a higher score for visual and auditory hallucinations than their male counterparts (Thorup et al, 2007), and patients with a positive family history of psychosis were more likely to have tactile hallucinations (Uçok and Bikmaz, 2007). Pertaining to clinical features, Evensen et al (2011) reported better cognitive insight in first-episode patients with hallucinations only compared to patients with delusions only.…”
Section: Introductionmentioning
confidence: 91%
“…Specific significance of hallucinations and delusions for diagnostic stability and illness course was observed in adults [11,20]. In our study hallucinations and suspiciousness were associated with further treatment but were not specific for schizophrenia diagnosis.…”
Section: Discussionsupporting
confidence: 44%
“…En høy grad av sykdomsinnsikt ser ut til å øke risikoen gjennom faktorer som negative antagelser om egen lidelse (liten tro på tilfriskning og at lidelsen kan kontrolleres) og negative tanker (håpløshet) når det gjelder framtiden (44;45). Et symptombilde preget av hallusinasjoner ser også ut til å innebaere høyere selvmordsrisiko (153), se kapittel 7 om utredning av selvmordsrisiko.…”
Section: Samtidige Somatiske Lidelserunclassified